Fermentation of ginkgo biloba kernel juice using Lactobacillus plantarum Y2 from the ginkgo peel: Fermentation characteristics and evolution of phenolic profiles, antioxidant activities in vitro, and volatile flavor compounds - Yang, Jie; Sun, Yue; Chen, Jinling; Cheng, Yu; Zhang, Haoran; Gao, Tengqi; Xu, Feng; Pan, Saikun; Tao, Yang; Lu, Jing (Frontiers in Nutrition, 2022)
In this work, a strain of Lactobacillus plantarum Y2 was isolated from the ginkgo peel, and that adapting well to the ginkgo biloba kernel juice. After 48 h of fermentation, the number of viable cells in the stable growth phase was remained at 10.0 LogCFU/mL, the content of total organic acid increased by 5.86%. Phenolic substances were significantly enriched, and the content of total phenolic substances increased by 9.72%, and the content of total flavonoids after fermentation exceeded 55.33 mg/L, which was 3.6 times that of unfermented ginkgo juice. The total relative content of volatile flavor compounds increased by 125.48%, and 24 new volatile flavor substances produced. The content of total sugar, total protein and total free amino acid decreased to 44.85%, 67.51% and 6.88%, respectively. Meanwhile, more than 82.25% of 4'-O-Methylpyridoxine was degraded under lactic acid fermentation, and the final concentration in ginkgo biloba kernel juice was lower than 41.53 mg/L. In addition, the antioxidant and antibacterial activities of fermented ginkgo biloba kernel juice were significantly enhanced. The results showed that LAB fermentation could effectively improve the nutritional value and safety of ginkgo biloba kernel juice.